2021
DOI: 10.1166/jbn.2021.3106
|View full text |Cite
|
Sign up to set email alerts
|

Repairing of Subchondral Defect and Articular Cartilage of Knee Joint of Rabbit by Gadolinium Containing Bio-Nanocomposites

Abstract: A variety of gadolinium (Gd) based nanoparticles (NPs) were synthesized due to the unique magnetic properties of Gd-containing rare earth compounds and the particularity of micro/nano-materials, which were then incorporated into hydroxyapatite (HA) to obtain inorganic-organic composite materials. Then, HA/Gd NPs containing slow-release transforming growth factor (TGF-β1) were harvested. Adipose-derived stem cells (ADSCs) were extracted from the adipose tissue of a four-month-old New Zealand white rabbit. HA/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Note: * indicated that the differences were statistically significant compared with those in the S3 group (P < 0:05), while # indicated the statistically significant differences compared with those in the S1 group (P < 0:05). Journal of Nanomaterials rabbit ADSCs in this study was relatively successful [22]. Alkaline phosphatase belongs to phosphate monoester hydrolase, a group of specific phosphatases.…”
Section: Discussionmentioning
confidence: 65%
“…Note: * indicated that the differences were statistically significant compared with those in the S3 group (P < 0:05), while # indicated the statistically significant differences compared with those in the S1 group (P < 0:05). Journal of Nanomaterials rabbit ADSCs in this study was relatively successful [22]. Alkaline phosphatase belongs to phosphate monoester hydrolase, a group of specific phosphatases.…”
Section: Discussionmentioning
confidence: 65%
“…Studies have reported that RE NMs, including Ce [ 16 , 114 ], Gd [ 10 , 22 , 115 ], Eu [ 116 ], La [ 13 ], Y [ 66 ], NaGdF 4 :Yb/Er NPs [ 12 ] and NaYF 4 :Yb/Er NPs [ 11 ], have high biocompatibility and can promote the proliferation of MSCs, preosteoblasts and osteoblasts. RE NMs have been shown to accelerate cell cycle progression [ 117 ] and promote mitotic spindle formation [ 12 ].…”
Section: Effects Of Re Nms On Osteogenesis and The Underlying Mechanismsmentioning
confidence: 99%